Adaptive Strategies of Digital Transformation on Students’ Consumptive Behavior in the Era of Society 5.0 - Sofi Reza Audry; Ila Navila (Cirebon International Journal of Economics and Business, 2023)
The digital era has seen consistent economic growth. The increasing number of online transactions every year shows this trend. One of the positive impacts of the development of the digital economy as a method for carrying out economic transactions is that it can increase knowledge and provide practicality in transactions. The progress of digitalization provides significant benefits in changing the order of economic behavior but will have negative impacts if not handled well. With the rapid development of E-commerce, it cannot be denied that crime in this field is on the rise in Indonesia, with fraud being the most common. Online fraud is essentially the same as traditional fraud; the difference lies in the way they operate, especially the use of electronic systems. This fraud can be interpreted as misuse of the news delivery system. The use of electronic media to display news, advertisements and other purposes that cause inconvenience to site users usually occurs without the victim's permission and is often undesirable. Consequently, adaptive strategies for this digital transformation are needed to increase awareness. Sharia Economics student IAIN Syekh Nurjati Cirebon was used as the research subject in this study. This research uses a qualitative approach, with data collection through interviews. According to the findings of this research, to avoid social media crimes in the era of society 5.0, knowledge of financial literacy and digital literacy is needed. Financial literacy is the ability to manage personal finances to avoid excessive consumption, while digital literacy is knowledge about how to use social media.